Surgical outcomes after gender-affirming hysterectomies: a consecutive case series of 72 patients - Susanna Alder; Kiriaki Papaikonomou; Leonora Tebani; Ilmatar Rooda; Cecilia Dhejne; Pauliina Damdimopoulou; Sebastian Gidlöf (Journal of Obstetrics and Gynaecology, 2025)
Background Hysterectomy is a significant component of gender-affirming treatment for transgender individuals. The choice of surgical technique and associated complications have been studied, but very few studies have used a standardised classification system to grade surgical complications. This study aimed to describe our hospital’s experience on gender-affirming hysterectomies with regards to patient demographics, surgical techniques, and postoperative complications using a validated classification system.Methods The study is a prospective follow-up case-series study of 72 consecutive patients undergoing gender-affirming hysterectomy at Karolinska University Hospital between 2016 and 2023. Patient demographics (age and mean body mass index), tobacco and alcohol habits, medical history and comorbidities, route of hysterectomy, complications and 30-days postoperative outcomes were reported. Surgical complications were graded according to the Clavien-Dindo classification system.Results The study population, with an average age of 27.6 years, presented diverse medical conditions, with psychiatric diagnoses being the most prevalent. The most common procedure was total laparoscopic hysterectomy, with low intraoperative blood loss. Surgical complications were rare, and primarily required minimal interventions. The 30-day Clavien-Dindo postoperative complication rate of grade II or higher was 19%, although only 4% experienced complications necessitating re-surgery (grade III or higher). Postoperative follow-up emerged as a critical aspect, with 22% of patients seeking non-elective medical attention within the first month, often due to vaginal bleeding or abdominal pain.Conclusions Our findings support the safety and feasibility of gender-affirming hysterectomies, particularly when performed laparoscopically, with very few severe complications observed using a validated scoring system. Extensive follow-up care, as well as addressing common postoperative concerns, is essential. Despite a relatively small sample size and lack of a control group, this study provides valuable insights into transgender healthcare from a previously unstudied region. Future research should preferably include larger cohorts, multicentre and registry-based studies.